Qualitative research for the information professional - Gorman, G. E. (Facet, 2005)
There is a long tradition of quantitative analysis in the information profession, but even the most seasoned professionals often find research design, execution, and evaluation intimidating. This companion volume to the authors' successful and highly-praised Qualitative Research for the Information Professional makes quantitative methods understandable and manageable. From research design to statistics, data evaluation to reporting, every phase of the process is covered. Additional chapters explore survey and experimental methodologies, the importance of relevant prior work, sample selection, adherence to method, and more. There is even guidance for studying data gathered from electronic resources. Each chapter includes focus questions, an introduction to the subject matter, clear explanations of complex issues, and relevant scenarios.